Some Beispiel and Ranker-zustand in Penalty Function - Dr. Amanpreet Singh, Salil Kumar, Shelja Jhamb (International Journal of Advanced Science and Technology, 2020)
The Hypothesis of penalty and barrier strategies is Straight forward . Within the penalty method we have to pay fine for violating the constraints, and get inexact solution of our unique issue by adjusting the objective function and a penalty term including the constraints. By expanding the penalty, the surmised arrangement is constrained to approach the feasible. For the barrier method, we have to move around within the interior of the feasible domain, and each time we try to approach the boundary. The force makes on halt near to the exact solution, in case this happens to be at the boundary as we know, typically the case for compelled issues. By debilitating the barrier steadily, we get approximate solutions which ideally converge to the precise arrangement space, the arrangement of the initial constrained problem.